2015
DOI: 10.1021/acsami.5b03228
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Bifunctional Fluorescent Carbon Dots from Garlic for Cellular Imaging and Free Radical Scavenging

Abstract: Nitrogen and sulfur codoped carbon dots (CDs) were prepared from garlic by a hydrothermal method. The as-prepared CDs possess good water dispersibility, strong blue fluorescence emission with a fluorescent quantum yield of 17.5%, and excellent photo and pH stabilities. It is also demonstrated that the fluorescence of CDs are resistant to the interference of metal ions, biomolecules, and high ionic strength environments. Combining with low cytotoxicity properties, CDs could be used as an excellent fluorescent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
250
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 554 publications
(266 citation statements)
references
References 59 publications
13
250
0
3
Order By: Relevance
“…This result coincides with previous reports that CQDs were able to stain both the cytoplasm and cell membrane but it was difficult to label the nucleus. 5 Thus, the CQDs were suggested to be internalized into the cells through endocytosis, similar to other CQDs reported previously. 19 Besides, it was found that the fluorescence …”
Section: Bioimaging Applicationssupporting
confidence: 83%
See 1 more Smart Citation
“…This result coincides with previous reports that CQDs were able to stain both the cytoplasm and cell membrane but it was difficult to label the nucleus. 5 Thus, the CQDs were suggested to be internalized into the cells through endocytosis, similar to other CQDs reported previously. 19 Besides, it was found that the fluorescence …”
Section: Bioimaging Applicationssupporting
confidence: 83%
“…4 Among them, hydrothermal treatment of natural precursors is a low-cost and convenient route to prepare CQDs. [5][6][7][8][9] However, most reported CQDs have a relatively low fluorescence quantum yield in comparison to inorganic semiconductor quantum dots. [10][11][12][13] To improve the fluorescent properties of CQDs, two kinds of modifications including surface functionalization and heteroatom doping were proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Many CD syntheses report the use of biomass, particularly sourced from plant matter, which is essentially a huge source of naturally derived polysaccharides combined with smaller amounts of other organic molecules, e.g., amino acids, which can act as dopant agents. Some examples include the use of garlic [50], orange juice [51], onion waste [52] and general kitchen waste [53]. For the purpose of this review, we will concentrate on describing examples where defined and commercially available polysaccharides are used for the synthesis of FCDs and how these materials compare to CDs made using their monomeric counterparts.…”
Section: Reviewmentioning
confidence: 99%
“…Many CDs manufacturing methods have been developed, including pyrolysis 26 , hydrothermal 27 , calcination 28 , microwave assisted 29 , and laser-assisted 30 . Various raw materials have been adopted for the preparation of quantum dots, including glucose 31 , garlic 32 , wool 8 , candle soot 33 , and graphite 34 . This range of materials and techniques suggests that restrictions on what can be used for quantum dot production are limited only by the imagination.…”
Section: Discussionmentioning
confidence: 99%